Application of a new coaxial bipolar electrode for the treatment of vertebral metastases: a pilot study in an ovine model - Salamanna, Francesca; Tschon, Matilde; Tedesco, Giuseppe; Martini, Lucia; Maglio, Melania; Cavazza, Luca; Dolciotti, Noemi; Rossano, Federico; Liberti, Micaela; Salati, Simona; Cadossi, Matteo; Donati, Davide Maria; et al. (Frontiers in Medicine, 2025)
IntroductionSpinal metastases account for approximately 90% of masses detected through spinal imaging. Therefore, it is imperative to advance therapies. Electroporation modifies the permeability of cancer cell membranes using electric energy, increasing the local uptake of chemotherapeutics and promoting local tumor control. The aim of this study was to evaluate the safety of delivering electrical pulses that induce tissue ablation using novel coaxial bipolar electrodes in healthy bone and clinically relevant structures in an ovine model.MethodsElectroporation was performed on sheep vertebral bodies (L2-L4) applying an electric field intensity sufficient to deliver at least 3,500 J/Kg, absorbed energy previously shown to be effective in ablating bone tissue. The study also examined the impact on surrounding sensitive structures, such as peripheral nerves and the spinal cord. Effectiveness and safety assessment was performed by clinical evaluation, histological analysis and numerical simulation.ResultsThe results showed that the ablation induced by electroporation was clearly visible 7 days after treatment. This was confirmed histologically by the absence of osteoblasts, the complete inhibition of bone apposition, the presence of pyknotic osteocytes and the empty lacunae. The absence of tetracycline fluorescence further confirmed the absence of bone tissue growth in the ablated area. Histomorphometric analysis showed a significant difference (p < 0.0005) in the ablated area between the L2 vertebral body (where the electric field was applied with a single bipolar electrode; ablation area: 99.56 ± 18.00 mm2) and L3 and L4 vertebrae (where the electric field was applied by 2 bipolar electrodes; ablation area: 238.97 ± 81.44 mm2). Computational modeling showed that the estimated ablation volume was 0.43 cm3 in L2 and 3.45 cm3 in L4. Furthermore, no deficits following the application of the electrical pulses were observed in spinal nerves and spinal cord.DiscussionIn agreement with these findings, temperature estimation based on computational simulation showed negligible increase in the spinal cord at the level of treated vertebra. Utilizing coaxial bipolar electrodes within the vertebral body through a transpedicular approach could offer a safe and minimally invasive procedure to treat spinal tumors and metastases, regardless of lesion size, while safeguarding critical neural structures.